The greatest love story ever told : an oral history - Mullally, Megan; Offerman, Nick, 1970- (Dutton, 2018)
The popular comedic couple trace the story of their relationship, sharing anecdotes, family photos, and secrets that reveal how they overcame considerable social differences through their shared values and mutual love of music and laughter.